Cervical cancer prevention in HIV-infected women in resource-limited settings. Issue 6 (November 2010) - Parham, Groesbeck
Groesbeck Parham is Professor of Gynecologic Oncology and Infectious Diseases in the Department of Medicine at the University of Alabama at Birmingham (AL, USA) and Director of the Centre for Infectious Disease Research in Zambia's Cervical Cancer Prevention Program. A native Alabamian, Parham received his BA (1970) from Oberlin College, OH, USA, and medical degree (1981) from the University of Alabama in Birmingham. He completed an obstetrics and gynecology residency (1985) at the University of Alabama in Birmingham, a urogynecology fellowship (1986) at the University of London, UK, and Khartoum Teaching Hospital, Sudan, and a gynecologic oncology fellowship (1988) at the University of California, Irvine, CA, USA. He is a board-certified gynecologic oncologist. Parham moved to Lusaka, Zambia, in 2005 to establish the Centre for Infectious Disease Research in Zambia's Cervical Cancer Prevention Program, which targets HIV-infected women. Before moving to Lusaka he served as director of the divisions of gynecologic oncology at Charles Drew University of Medicine and Science in Los Angeles, CA, USA, and the University of Arkansas for Medical Sciences in Little Rock, AR, USA. His primary research interest is the science of implementing cancer prevention technology in post-colonial Africa.